ALUMINUM ALLOY SUBSTRATE FOR MAGNETIC DISK AND MAGNETIC DISK USING THE ALUMINUM ALLOY SUBSTRATE FOR MAGNETIC DISK

By controlling the composition and manufacturing processes to minimize Si-K-O and Ti-B particles, the aluminum alloy substrate achieves a smooth Ni-P plating film, addressing the issues of intermetallic compound fall-off and environmental contaminants, thereby improving magnetic disk recording density.

JP7620621B2Active Publication Date: 2025-01-23UACJ CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022514091
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-06
Filing Date
2021-04-06
Publication Date
2025-01-23
Estimated Expiration
2041-04-06

AI Technical Summary

Technical Problem

Existing methods for manufacturing magnetic disk substrates using JIS A5086 alloy result in the formation of intermetallic compounds that can fall off during processing, leading to depressions and scratches, which degrade the smoothness of the Ni-P plating film, and there are no effective countermeasures for dust and environmental contaminants.

Method used

An aluminum alloy substrate with controlled compositions and manufacturing processes to minimize Si-K-O and Ti-B particles, ensuring a smooth surface by limiting their presence to less than 1/6000 mm², combined with a Ni-P plating and magnetic layer configuration.

Benefits of technology

The solution effectively suppresses the formation of plating pits, resulting in a highly smooth Ni-P plating film with improved adhesion and reduced substrate damage, enhancing the recording density of magnetic disks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620621000003
    Figure 0007620621000003
  • Figure 0007620621000001
    Figure 0007620621000001
  • Figure 0007620621000002
    Figure 0007620621000002
Patent Text Reader

Abstract

Provided are: an aluminum alloy substrate for a magnetic disk; and a magnetic disk using same. The aluminum alloy substrate is composed of an aluminum alloy containing 1.0-6.5 mass% of Mg, with the remainder comprising Al and inevitable impurities, wherein the distribution of Si-K-O-based particles having a maximum diameter of at least 1 μm adhering to the surface from the surrounding environment is not more than 1 / 6000 mm2, and the distribution of Ti-B-based particles having a maximum diameter of at least 1 μm on the surface is not more than 1 / 6000 mm2.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminum alloy substrate for magnetic disks, which has excellent impact resistance and a Ni-P plating film with excellent smoothness, and to a magnetic disk using the aluminum alloy substrate for magnetic disks. [Background technology]

[0002] Hard disk drives (hereinafter abbreviated as "HDD") are widely used as storage devices in electronic devices such as computers and video recorders. HDDs incorporate magnetic disks for recording data. The magnetic disk has a circular magnetic disk substrate made of an aluminum alloy, a Ni-P plating film covering the surface of the magnetic disk substrate, and a magnetic layer laminated on the Ni-P plating film.

[0003] In recent years, the amount of information recorded on HDDs has been increasing, both in commercial use such as servers and data centers, and in home use such as personal computers and video recorders. In order to increase the capacity of HDDs in response to this situation, there is a demand to increase the recording density of the magnetic disks incorporated in the HDDs. In order to increase the recording density of the magnetic disks, it is necessary to form a smooth Ni-P plating film on the magnetic disk substrate.

[0004] Magnetic disks are usually manufactured by the following method. First, a rolled aluminum alloy plate is punched into a circular shape to manufacture a disk blank. Next, the disk blank is heated while being pressed from both sides in the thickness direction to reduce the warping of the disk blank. After that, the disk blank is cut and ground to be formed into a desired shape to obtain a magnetic disk substrate. The magnetic disk substrate thus obtained is sequentially subjected to a pretreatment for forming a Ni-P plating film, an electroless Ni-P plating process, and sputtering of a magnetic layer, thereby manufacturing a magnetic disk.

[0005] JIS A5086 alloy is widely used as an aluminum alloy for magnetic disk substrates. However, when disk blanks are made with the general composition range of JIS A5086 alloy, relatively large intermetallic compounds may be formed in the Al matrix. Such intermetallic compounds may fall off from the Al matrix during cutting, grinding, and pretreatment for forming Ni-P plating film.

[0006] When the intermetallic compounds fall off from the Al matrix, relatively large depressions are formed on the magnetic disk substrate. In addition, when the intermetallic compounds that fall off from the magnetic disk substrate are sandwiched between a tool and the magnetic disk substrate during cutting or grinding, scratches may be formed on the magnetic disk substrate. If electroless Ni-P plating is performed in such a state, depressions called plating pits may be formed in the Ni-P plating film due to the depressions and scratches on the magnetic disk substrate, which may lead to a decrease in the smoothness of the Ni-P plating film.

[0007] Therefore, in order to further improve the smoothness of the Ni-P plating film, various techniques for reducing foreign matter such as intermetallic compounds in the magnetic disk substrate have been studied. For example, Patent Document 1 describes a method for producing an Al-based alloy plate for a magnetic disk, which is characterized by continuously casting an Al-based alloy melt essentially containing 2-6% Mg, 1% or less Mn, 0.3% or less Fe, 0.25% or less Zn, and 0.35% or less Cr to a plate thickness of 4-15 mm, and further rolling it.

[0008] Patent Document 2 describes a method for treating aluminum or an aluminum alloy, in which B is added to a molten aluminum or aluminum alloy containing Ti and Zr as impurities in an amount 100 to 200 massppm more than the total chemical equivalent calculated as TiB2 and ZrB2. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Japanese Patent Application Publication No. 56-105846 [Patent Document 2] JP 2002-173718 A

[0010] According to the manufacturing method of Patent Document 1, by reducing the thickness of the plate material during casting, the cooling rate when the molten metal solidifies can be increased, and the Al-Fe-Mn intermetallic compounds can be refined. However, the manufacturing method of Patent Document 1 has a problem in that it is difficult to sufficiently refine inclusions other than the Al-Fe-Mn intermetallic compounds.

[0011] The treatment method of Patent Document 2 adds an excess amount of B to Ti and Zr in an Al-based alloy melt in an aluminum casting process, and then removes inclusions such as TiB2 and ZrB2 formed by reaction with B. However, the method of Patent Document 2 has a problem in that foreign matter other than Ti-B and Zr-B has an adverse effect.

[0012] Furthermore, regarding the adhesion of dust and the like from the surrounding environment to the surface of the aluminum plate during the manufacturing process of the aluminum plate, there are no detailed reports on the cause and methods of dealing with this. Summary of the Invention [Problem to be solved by the invention]

[0013] The present invention has been made in view of the above problems. The present inventors have discovered that an aluminum alloy substrate for magnetic disks having an excellent smoothness of a Ni-P plating film can be obtained by suppressing adhesion to the surface of an aluminum alloy substrate of coarse Ti-B-based particles formed from unavoidable impurities contained in an aluminum alloy, and Si-KO-based particles contained in dust and the like from the surrounding environment during the manufacturing process, and have thus completed the present invention. [Means for solving the problem]

[0014] That is, in claim 1, the present invention is an aluminum alloy containing 1.0 to 6.5 mass% Mg, the balance being Al and unavoidable impurities, and the distribution of Si-KO type particles having a maximum diameter of 1 μm or more attached to the surface from the surrounding environment is 1 particle or less per 6000 mm 2 The distribution of Ti-B particles with a maximum diameter of 1 μm or more on the surface is 1 particle / 6000 mm or less. 2 The aluminum alloy substrate for a magnetic disk is characterized in that

[0015] In claim 2 of the present invention, in claim 1, the aluminum alloy further contains one or more selected from the group consisting of Cu: 0.300 mass% or less, Zn: 0.60 mass% or less, Fe: 0.600 mass% or less, Si: 0.600 mass% or less, Be: 0.0020 mass% or less, Cr: 0.20 mass% or less, Mn: 1.70 mass% or less, Zr: 0.20 mass% or less, Sr: 0.10 mass% or less, Na: 0.10 mass% or less, and P: 0.10 mass% or less.

[0016] In claim 3, the present invention provides a magnetic disk characterized in that an electroless Ni-P plating layer and a magnetic layer thereon are provided on the surface of the aluminum alloy substrate for magnetic disk according to claim 1 or 2. Effect of the Invention

[0017] The aluminum alloy substrate for magnetic disk according to the present invention suppresses the generation of Si-KO-based particles and Ti-B-based particles having a maximum diameter of 1 μm or more, and reduces damage to the substrate surface caused by the falling off of these particles, thereby making it possible to form a Ni-P plating film with few plating pits and high smoothness. [Brief description of the drawings]

[0018] [Figure 1] 1 is a scanning ion microscope photograph showing a cross section of an aluminum alloy substrate after plating. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] A. Aluminum alloy substrates for magnetic disks The aluminum alloy substrate for magnetic disks according to the present invention (hereinafter, sometimes referred to as "aluminum alloy substrate") will be described. The aluminum alloy substrate is obtained by preparing an aluminum alloy plate using an aluminum alloy having a predetermined alloy composition, punching this into a disk blank, and further subjecting the blank to pressure flattening treatment, cutting processing, and grinding processing.

[0020] A-1. Alloy composition of aluminum alloy plate The composition of the aluminum alloy used for the aluminum alloy plate and the reasons for limiting it will be described in detail below.

[0021] Mg: 1.0~6.5mass% Mg is contained as an essential element in aluminum alloys, and mainly exerts an effect of improving the strength of aluminum alloy substrates. In addition, since the zincate film during zincate treatment is uniformly, thinly, and densely adhered, it improves the smoothness of the plating surface made of Ni-P in the plating process, which is the next process of the zincate treatment process. However, if the Mg content is less than 1.0 mass% (hereinafter simply written as "%)", the strength is insufficient and it deforms during cutting and grinding. Furthermore, the zincate film formed by the zincate treatment becomes non-uniform, and the adhesion and smoothness of the plating are reduced. On the other hand, if the Mg content exceeds 6.5%, coarse Al-Mg-based intermetallic compounds are formed, and during etching, zincate treatment, and cutting and grinding, the intermetallic compounds fall off and large dents are generated, and the smoothness of the plating surface is reduced. In addition, if the Mg content is too high, the strength of the aluminum alloy substrate becomes higher, and cracks are generated during rolling. Therefore, the Mg content is specified to be 1.0 to 6.5%. From the viewpoint of a balance between strength and manufacturability, the Mg content is preferably 3.0 to 5.0%, and more preferably 3.5 to 4.5%.

[0022] The aluminum alloy may further contain, in addition to Mg, one or more selected from the group consisting of Cu, Zn, Fe, Si, Be, Cr, Mn, Zr, Sr, Na, and P as further optional elements.

[0023] Cu:0.300% or less The aluminum alloy may contain 0.300% or less Cu as an optional element. Cu has the effect of suppressing the elution of Al from the aluminum alloy substrate when zincating is performed in the manufacturing process of the magnetic disk. By making the Cu content 0.300% or less, a Zn film that is dense, thin, and has little variation in thickness can be attached to the surface of the aluminum alloy substrate when zincating is performed in the manufacturing process of the magnetic disk. By forming such a Zn film, a smooth Ni-P plating film can be formed by the subsequent electroless Ni-P plating process.

[0024] However, if the Cu content is too high, the corrosion resistance of the aluminum alloy substrate is reduced, and a region where Al is easily dissolved locally is formed. Therefore, when zincate treatment is performed in the manufacturing process of the magnetic disk, the amount of Al dissolved on the surface of the aluminum alloy substrate is uneven, and the thickness of the Zn film is likely to vary greatly. As a result, there is a risk of causing a decrease in the adhesion between the Ni-P plating film and the aluminum alloy substrate and a decrease in the smoothness of the Ni-P plating film.

[0025] By making the Cu content in the aluminum alloy 0.300% or less, preferably 0.150% or less, the formation of plating pits can be suppressed and the smoothness of the Ni-P plating film can be further improved. The lower limit of the Cu content is preferably 0.005%, more preferably 0.010%. The Cu content may be 0% (0.000%).

[0026] Zn: 0.60% or less The aluminum alloy may contain 0.60% or less Zn as an optional element. Zn, like Cu, has the effect of suppressing the elution of Al from the aluminum alloy substrate during zincate treatment. By making the Zn content 0.60% or less, a dense, thin Zn film with small thickness variation can be attached to the surface of the aluminum alloy substrate when zincate treatment is performed in the manufacturing process of the magnetic disk. Then, by forming such a Zn film, a smooth Ni-P plating film can be formed by the subsequent electroless Ni-P plating process.

[0027] However, if the Zn content is too high, the corrosion resistance of the aluminum alloy substrate is reduced, and a region where Al is easily dissolved locally is formed. Therefore, when zincate treatment is performed in the manufacturing process of the magnetic disk, the amount of Al dissolved on the surface of the aluminum alloy substrate is uneven, and the thickness of the Zn film is likely to vary greatly. As a result, there is a risk of causing a decrease in the adhesion between the Ni-P plating film and the aluminum alloy substrate and a decrease in the smoothness of the Ni-P plating film.

[0028] By making the Zn content in the aluminum alloy 0.60% or less, preferably 0.50% or less, the formation of plating pits can be suppressed and the smoothness of the Ni-P plating film can be further improved. The lower limit of the Zn content is preferably 0.10%, more preferably 0.25%. The Zn content may be 0% (0.00%).

[0029] Fe, Si: 0.600% or less The aluminum alloy may contain 0.600% or less Fe and Si as optional elements. Fe is hardly dissolved in the Al matrix and is dispersed in the aluminum alloy substrate as an Al-Fe intermetallic compound. When the aluminum alloy contains Mg, Si forms an Mg-Si intermetallic compound with Mg.

[0030] If such Al-Fe intermetallic compounds or Mg-Si intermetallic compounds fall off from the surface of the aluminum alloy substrate, plating pits are likely to be formed in the subsequent electroless Ni-P plating process. By making the Fe and Si contents in the aluminum alloy 0.600% or less, preferably 0.050% or less, more preferably 0.001% or less, respectively, the amount of the intermetallic compounds present in the aluminum alloy substrate can be further reduced. As a result, the formation of plating pits can be suppressed and the smoothness of the Ni-P plating film can be further improved.

[0031] In order to suppress the occurrence of plating pits due to the above-mentioned intermetallic compounds, it is preferable to reduce the contents of Fe and Si. However, these elements are contained not only in general purity ingots but also in high purity ingots with an Al purity of 99.9 mass% or more. Therefore, if an aluminum alloy substrate containing almost no Fe or Si is to be produced, a special treatment for removing these elements during casting is required, which leads to an increase in the production cost of the aluminum alloy substrate.

[0032] If the Fe and Si contents in the aluminum alloy are each 0.050% or less, preferably 0.001% or less, the aluminum alloy substrate can be produced without performing special treatment to remove these elements. As a result, the smoothness of the Ni-P plating film can be further improved while avoiding an increase in the manufacturing cost of the aluminum alloy substrate. Also, if the Fe and Si contents in the aluminum alloy are each more than 0.050% but 0.600% or less, the aluminum alloy substrate can be produced using a base metal with a lower purity. This allows the material cost of the aluminum alloy substrate to be further reduced. The Fe and Si contents may each be 0% (0.000%).

[0033] Be: 0.0020% or less Be is an element added to the molten metal when casting an aluminum alloy containing Mg in order to suppress oxidation of Mg. In addition, by making the Be content in the aluminum alloy 0.0020% or less, the Zn film formed on the surface of the aluminum alloy substrate during the manufacturing process of the magnetic disk can be made denser and the variation in thickness can be reduced. As a result, the smoothness of the Ni-P film formed on the aluminum alloy substrate can be improved.

[0034] However, if the aluminum alloy contains too much Be, Be-based oxides are likely to form on the surface of the disk blank when the disk blank is heated during the manufacturing process of the aluminum alloy substrate. Also, if the aluminum alloy further contains Mg, Al-Mg-Be-based oxides are likely to form on the surface of the disk blank when the disk blank is heated. If the amount of these oxides is large, the Zn coating thickness will vary greatly, which may lead to the occurrence of plating pits.

[0035] By making the Be content in the aluminum alloy 0.0020% or less, preferably 0.0010% or less, the amount of Al-Mg-Be oxides can be reduced and the smoothness of the Ni-P plating film can be further improved. The lower limit of the Be content may be 0% (0.0000%), but is preferably 0.0002%.

[0036] Cr:0.20% or less The aluminum alloy may contain 0.20% or less Cr as an optional element. A part of Cr is dispersed in the aluminum alloy substrate as fine intermetallic compounds formed during casting. Cr that does not form intermetallic compounds during casting dissolves in the Al matrix and has the effect of improving the strength of the aluminum alloy substrate by solid solution strengthening.

[0037] In addition, Cr has the effect of improving the machinability and grindability and refining the recrystallized structure, thereby improving the adhesion between the aluminum alloy substrate and the Ni-P plating film and suppressing the occurrence of plating pits.

[0038] However, if the Cr content in the aluminum alloy is too high, coarse Al-Cr intermetallic compounds are likely to be formed in the aluminum alloy substrate, and if such coarse Al-Cr intermetallic compounds fall off from the surface of the aluminum alloy substrate, plating pits are likely to be formed in the subsequent electroless Ni-P plating process.

[0039] By making the Cr content in the aluminum alloy 0.20% or less, preferably 0.10% or less, it is possible to suppress the formation of plating pits, form a smooth Ni-P plating film, and further improve the strength of the aluminum alloy substrate. The lower limit of the Cr content is preferably 0.03%, more preferably 0.05%. The Cr content may be 0% (0.00%).

[0040] Mn: 1.70% or less The aluminum alloy may contain 1.70% or less Mn as an optional element. A part of Mn is dispersed in the aluminum alloy substrate as fine intermetallic compounds formed during casting. Mn that is not formed into intermetallic compounds during casting dissolves in the Al matrix and has the effect of improving the strength of the aluminum alloy substrate by solid solution strengthening.

[0041] In addition, Mn has the effect of improving the machinability and grindability and refining the recrystallized structure, which results in improved adhesion between the aluminum alloy substrate and the Ni-P plating film and suppresses the occurrence of plating pits.

[0042] However, if the Mn content in the aluminum alloy is too high, coarse Al-Mn intermetallic compounds are likely to be formed in the aluminum alloy substrate, and if such coarse Al-Mn intermetallic compounds fall off from the surface of the aluminum alloy substrate, plating pits are likely to be formed in the subsequent electroless Ni-P plating process.

[0043] In this way, by making the Mn content in the aluminum alloy 1.70% or less, preferably 1.20% or less, it is possible to suppress the formation of plating pits, form a smooth Ni-P plating film, and further improve the strength of the aluminum alloy substrate. The lower limit of the Mn content is preferably 0.10%, more preferably 0.15%. The Mn content may be 0% (0.00%).

[0044] Zr: 0.20% or less The aluminum alloy may contain 0.20% or less Zr as an optional element. A part of Zr is dispersed in the aluminum alloy substrate as fine intermetallic compounds formed during casting. Zr that does not form intermetallic compounds during casting dissolves in the Al matrix and has the effect of improving the strength of the aluminum alloy substrate by solid solution strengthening.

[0045] Zr also acts to improve machinability and grindability and to refine the recrystallized structure, thereby improving the adhesion between the aluminum alloy substrate and the Ni-P plating film and suppressing the occurrence of plating pits.

[0046] However, if the Zr content in the aluminum alloy is too high, coarse Al-Zr intermetallic compounds are likely to be formed in the aluminum alloy substrate, and if such coarse Al-Zr intermetallic compounds fall off from the surface of the aluminum alloy substrate, plating pits are likely to be formed in the subsequent electroless Ni-P plating process.

[0047] By setting the Zr content in the aluminum alloy to 0.20% or less, the formation of plating pits can be suppressed, a smooth Ni-P plating film can be formed, and the strength of the aluminum alloy substrate can be further improved. The lower limit of the Zr content is preferably 0.03%, more preferably 0.05%. The Zr content may be 0% (0.00%).

[0048] Sr, Na and P: 0.10% or less each Sr, Na, and P have the effect of refining second phase particles (mainly Si particles) in the aluminum alloy substrate and improving plating properties. They also have the effect of reducing the non-uniformity of the size of second phase particles in the aluminum alloy substrate and reducing the variation in impact resistance properties. Therefore, the aluminum alloy may contain 0.10% or less of each of Sr, Na, and P.

[0049] However, even if each of Sr, Na, and P is contained in excess of 0.10%, the above effects are saturated and no further significant effects are obtained. In order to obtain the above effects, it is preferable that the lower limit of each of Sr, Na, and P is 0.001%. The content of each of Sr, Na, and P may be 0% (0.000%).

[0050] Other elements The aluminum alloy may contain elements that are inevitable impurities other than the essential and optional components described above. Examples of these elements include Ti, B, Si, Ga, etc., and the effects of the present invention are not impaired if the content of each element other than B is 0.05% or less, and the total content is 0.15% or less. The effects of the present invention are not impaired if the content of B is 0.0015% or less. Here, when Ti and B are contained, "Ti-B-based particles" described later are formed. As described above, in the present invention, Si can be actively added as an optional component, but there are also cases where it is not added. As for Si, as described above, it is contained as an inevitable impurity not only in general purity ingots but also in high purity ingots with an Al purity of 99.9% or more, and even when it is contained as an inevitable impurity, the effects of the present invention are not impaired if the content is 0.050% or less (preferably 0.001% or less) as described above.

[0051] A-2. Manufacturing method of aluminum alloy plate (1) Casting process The raw material of the aluminum material having the above alloy composition is melted, and the molten metal is cast to produce an ingot. For casting, semi-continuous casting (DC casting), metal mold casting, and continuous casting (CC casting) are used. In DC casting, the molten metal poured through a spout loses heat to the bottom block, the water-cooled mold wall, and cooling water directly discharged onto the outer periphery of the ingot, solidifies, and is drawn downward as an ingot. In metal mold casting, the molten metal poured into a hollow mold made of cast iron or the like loses heat to the mold wall, solidifies, and an ingot is produced. In CC casting, the molten metal is supplied through a casting nozzle between a pair of rolls (or belt casters, block casters), and a thin plate is directly cast by extracting heat from the rolls.

[0052] In such a casting process, it is preferable to carry out in-line a degassing treatment for reducing dissolved gas in the molten metal and a filtration treatment for removing solid matter in the molten metal.

[0053] For example, the degassing process may be a process called the SNIF (Spinning Nozzle Inert Flotation) process or the Alpur process. In these processes, a process gas such as argon gas or a mixed gas of argon and chlorine is blown into the molten metal while stirring the molten metal at high speed with a rotor with blades, forming fine bubbles of the process gas in the molten metal. This makes it possible to remove hydrogen gas and inclusions dissolved in the molten metal in a short time. An in-line degassing device may be used for the degassing process.

[0054] For example, the filtration process may be a cake filtration process, a filter medium filtration process, etc. For example, a filter such as a ceramic tube filter, a ceramic foam filter, or an alumina ball filter may be used for the filtration process.

[0055] (2) Homogenization process After the ingot is produced, the ingot may be subjected to surface grinding and homogenization treatment as necessary before hot rolling. The holding temperature in the homogenization treatment may be appropriately set within the range of, for example, 500 to 600° C. The holding time in the homogenization treatment may be appropriately set within the range of, for example, 1 to 60 hours.

[0056] (3) Hot rolling process Next, the ingot is hot-rolled to produce a hot-rolled sheet. The rolling conditions for the hot rolling are not particularly limited, but for example, the hot rolling can be performed with a start temperature in the range of 400 to 600°C and an end temperature in the range of 260 to 380°C.

[0057] (4) Cold rolling process After the hot rolling, the obtained hot rolled sheet is subjected to one or more passes of cold rolling to obtain a cold rolled sheet. The rolling conditions of the cold rolling are not particularly limited and may be appropriately set according to the desired thickness and strength of the aluminum alloy substrate. For example, the total rolling reduction in the cold rolling may be 20 to 95%. The thickness of the cold rolled sheet may be appropriately set, for example, within the range of 0.2 to 1.9 mm.

[0058] (5) Annealing process In the manufacturing method of the above embodiment, annealing may be performed, if necessary, at least either before the first pass of cold rolling or between passes. The annealing may be performed using a batch-type heat treatment furnace or a continuous heat treatment furnace. When a batch-type heat treatment furnace is used, the holding temperature during annealing is preferably set to 250 to 430°C and the holding time is preferably set to 0.1 to 10 hours. When a continuous heat treatment furnace is used, the residence time in the furnace is preferably set to 60 seconds or less and the temperature in the furnace is preferably set to 400 to 500°C. By performing the annealing treatment under such conditions, the workability during cold rolling can be restored. Through the above steps, an aluminum alloy plate is produced.

[0059] A-3. Manufacturing method of aluminum alloy substrate When producing an aluminum alloy substrate from the above aluminum alloy plate, for example, the following method can be adopted. First, a disk blank having a circular ring shape is produced by punching the aluminum alloy plate. Then, the disk blank is heated while being pressurized from both sides in the thickness direction to perform pressure annealing, thereby reducing distortion of the disk blank and improving flatness. The holding temperature and pressure in the pressure annealing can be appropriately selected from the ranges of, for example, 250 to 430°C and 1.0 to 3.0 MPa. The holding time in the pressure annealing can be, for example, 30 minutes or more.

[0060] After pressure annealing, the disk blank is cut and ground to produce an aluminum alloy substrate having a desired shape. After these processes, if necessary, a stress relief heat treatment may be performed at 150 to 350°C for 0.1 to 5.0 hours to remove stress generated during processing. Through the above steps, an aluminum alloy substrate is produced.

[0061] A-4. Particles present on the surface of the aluminum alloy substrate On the surface of the aluminum alloy substrate, there are particles that are mixed in from the surrounding environment during the manufacturing process of the aluminum alloy plate or the manufacturing process of the aluminum alloy substrate, as described below, and there are also particles derived from the aluminum alloy components. Among these particles, when coarse particles having a maximum diameter of 1 μm or more fall off the surface of the aluminum alloy substrate during the manufacturing process of the magnetic disk, large depressions are formed on the surface, and particles that fall off the surface during cutting or grinding are dragged between the tool and the aluminum alloy substrate, damaging the surface of the aluminum alloy substrate. If electroless Ni-P plating is performed in a state where such depressions or scratches exist, plating pits are formed on the surface of the Ni-P plating film, and the smoothness of the Ni-P plating film is impaired. Therefore, it is necessary to suppress the generation of such coarse particles. The present inventors have found that such coarse particles include Si-KO-based particles mixed in from the surrounding environment and Ti-B-based particles derived from the aluminum alloy components.

[0062] (1) Si-KO particles on the surface of aluminum alloy substrate Si-K (potassium)-O (oxygen) particles are dispersed on the surface of the aluminum alloy substrate. The number of Si-KO particles with a maximum diameter of 1 μm or more among the Si-KO particles present on the surface of the aluminum alloy substrate is 1 per 6000 mm. 2 It is regulated as follows:

[0063] Si-KO particles with a maximum diameter of 1 μm or more are 1 particle / 6000 mm 2If the number of Si-KO particles is more than 100, coarse Si-KO particles are present on the surface of the aluminum alloy substrate. If such Si-KO particles fall off the surface during the manufacturing process of the magnetic disk, large pits are formed on the surface of the aluminum alloy substrate. If the Si-KO particles that fall off the surface during cutting or grinding are dragged between the tool and the aluminum alloy substrate, scratches may occur on the surface of the aluminum alloy substrate. If electroless Ni-P plating is performed in a state where such pits or scratches exist, plating pits are likely to be formed on the surface of the Ni-P plating film. Figure 1 is a scanning ion microscope photograph showing the cross section of an aluminum alloy substrate after plating, and it can be seen that plating pits are formed when Si-KO particles are present. To further explain Figure 1, the position of the plating pit shown at the top of the figure was occupied by Si-KO particles as shown in the figure, and some of the particles fell off the surface during the manufacturing process of the magnetic disk and became pits, and these pits form plating pits on the surface of the Ni-P plating film by the subsequent electroless Ni-P plating process.

[0064] The number of Si-KO particles with a maximum diameter of 1 μm or more is 1 / 6000 mm 2 By setting the number of Si-KO particles to 0 or less, the generation of coarse Si-KO particles in the aluminum alloy substrate is suppressed. As a result, a Ni-P plating film with few plating pits and high smoothness can be formed in the electroless Ni-P plating process. From the viewpoint of further improving the smoothness of the Ni-P plating film, it is preferable that there are no Si-KO particles with a maximum diameter of 1 μm or more on the surface of the aluminum alloy substrate, that is, 0 particles / 6000 mm 2 It is preferable that the Si-KO particles are present on the surface of the aluminum alloy substrate, but if the longest diameter of the particles is less than 1 μm, there is no problem. If the longest diameter is less than 1 μm, the depressions and scratches formed on the surface are small as described above, and the plating pits formed on the surface of the Ni-P plating film are also small and do not pose a problem.

[0065] The Si-KO-based particles are formed when dust or the like present in the environment surrounding the roll device or punching device (hereinafter referred to as the "ambient environment") drifts onto the surface of the aluminum alloy plate due to air convection or vibration of the device during processing using rolls such as rolling or leveling in the manufacture of the aluminum alloy plate, or during punching of disk blanks, and then finally adheres to the surface of the aluminum alloy substrate through subsequent processing. In the present invention, such Si-KO-based particles are referred to as Si-KO-based particles adhered to the surface from the ambient environment.

[0066] In particular, when using rolls for hot rolling or cold rolling in the manufacture of aluminum alloy sheets, dust and the like present in the surrounding environment adhere to the surface of the rolled sheet due to vibration caused by the operation of the rolls, and are embedded in the surface in the subsequent process. In addition, when punching out a disk blank from an aluminum alloy sheet, punching is performed intermittently, so dust and the like adhere to the surface due to the vibration, and are embedded in the surface during the subsequent pressure annealing. It is difficult to completely remove dust and the like that adheres when using rolls or punching out, but as described above, Si-KO-based particles with a maximum diameter of less than 1 μm do not affect the smoothness of the Ni-P plating film. As a method for suppressing the generation of Si-KO-based particles, it is effective to install a protective cover around the device or to install the device in an environment with little dust and the like. In addition, it is preferable to use polyvinyl chloride, acrylic resin, glass, etc. as the protective cover. If the distance between the protective cover and the device is too far, the effect of preventing contamination is small, and if it is too close, there is a risk that foreign matter attached to the protective cover will fall and become mixed in. Therefore, it is preferable to set the distance between the protective cover and the device to 0.5 to 6.0 m. More preferably, it is 1.0 to 5.5 m.

[0067] By taking the above measures, it is possible to significantly suppress the generation of Si-KO-based particles, but it is more preferable to carry out chemical treatment in case a trace amount of Si-KO-based particles are mixed in. If chemical treatment is carried out, it is preferable to carry out the treatment before grinding. The chemical treatment is preferably carried out using an aqueous solution of sulfuric acid or the like. If the concentration of the chemical treatment solution is less than 0.1%, the removal of Si-KO-based particles may be insufficient, and if it exceeds 1.0% or the temperature of the chemical treatment solution exceeds 40°C, the reaction may become active, holes may open on the plate surface, and the smoothness of the plated surface may decrease. Therefore, it is preferable to carry out cleaning with a chemical treatment solution of 0.1 to 1.0% at 40°C or less. In addition, the concentration of the chemical treatment solution is preferably in the range of 0.2 to 0.8%, and the temperature is preferably 30°C or less. If the temperature is 5°C or less, the effect of removing Si-KO-based particles cannot be sufficiently obtained. In addition, the processing time of the chemical cleaning is preferably 5 seconds or more. If the processing time is short, the removal of Si-KO-based particles may be insufficient. There is no particular upper limit on the processing time, but since manufacturing costs increase if the processing time is too long, the upper limit is set to about 100 seconds.

[0068] The Si-KO-based particles thus attached to the surface of the aluminum alloy substrate refer to particles in which Si, K, and O are detected when elemental analysis is performed using a SEM (scanning electron microscope) equipped with an EDS (energy dispersive X-ray spectrometer). In the present invention, the longest diameter of the Si-KO-based particles is defined as the distance between the two most distant points on the contour line of the Si-KO-based particles in a surface image of the aluminum alloy substrate taken by SEM.

[0069] A-5. Ti-B particles on the surface of aluminum alloy substrate Ti-B particles are dispersed on the surface of the aluminum alloy substrate. The number of Ti-B particles with a maximum diameter of 1 μm or more among the Ti-B particles present on the surface of the aluminum alloy substrate is 1 per 6000 mm. 2 It is regulated as follows:

[0070] Ti-B particles with a maximum diameter of 1 μm or more are 1 particle per 6000 mm 2If the number of Ti-B particles is more than 100, coarse Ti-B particles are present on the surface of the aluminum alloy substrate. If such Ti-B particles fall off the surface during the manufacturing process of the magnetic disk, large depressions are formed on the surface of the aluminum alloy substrate. If the Ti-B particles that fall off the surface during cutting or grinding are dragged between the tool and the aluminum alloy substrate, scratches may occur on the surface of the aluminum alloy substrate. If electroless Ni-P plating is performed in a state where such depressions or scratches exist, plating pits are likely to be formed on the surface of the Ni-P plating film.

[0071] The number of Ti-B particles with a maximum diameter of 1 μm or more is 1 / 6000 mm 2 By setting the number of Ti-B particles to 0 or less, the generation of coarse Ti-B particles in the aluminum alloy substrate is suppressed. As a result, a Ni-P plating film with few plating pits and high smoothness can be formed in the electroless Ni-P plating process. From the viewpoint of further improving the smoothness of the Ni-P plating film, it is preferable that there are no Ti-B particles with a maximum diameter of 1 μm or more on the surface of the aluminum alloy substrate, that is, 0 particles / 6000 mm 2 It is preferable that the Ti-B particles are present on the surface of the aluminum alloy substrate, but if the longest diameter of the Ti-B particles is less than 1 μm, there is no problem. If the longest diameter is less than 1 μm, the depressions and scratches formed on the surface are small as described above, and the plating pits formed on the surface of the Ni-P plating film are also small and do not pose a problem.

[0072] In addition, Ti-B-based particles containing at least both Ti and B are different from the above-mentioned Si-KO-based particles, and are formed by Ti and B as inevitable impurities contained in the aluminum alloy used in the smelting process of the aluminum alloy molten metal, which is the manufacturing process of the aluminum alloy plate, and are finally formed in the aluminum alloy substrate including the surface through subsequent processing. Although it is difficult to completely remove such Ti-B-based particles, as described above, Ti-B-based particles with a maximum diameter of less than 1 μm do not affect the smoothness of the Ni-P plating film. In order to suppress the generation of Ti-B-based particles, it is effective to use raw materials with low Ti and B contents. In other words, it is preferable to limit the contents of Ti and B as inevitable impurities contained in the aluminum alloy to 0.05% or less and 0.0015% or less, respectively.

[0073] The Ti-B based particles thus attached to the surface of the aluminum alloy substrate refer to particles in which Ti and B are detected when elemental analysis is performed using a SEM (scanning electron microscope) equipped with an EDS (energy dispersive X-ray spectrometer). In the present invention, the longest diameter of the Ti-B based particles is defined as the distance between the two most distant points on the contour line of the Ti-B based particles in a surface image of the aluminum alloy substrate taken by the SEM.

[0074] B. Magnetic disk B-1. Magnetic Disk Configuration The magnetic disk having the aluminum alloy substrate has, for example, the following configuration: the magnetic disk has an aluminum alloy substrate, a Ni-P plating film covering the surface of the aluminum alloy substrate, and a magnetic layer laminated on the Ni-P plating film.

[0075] The magnetic disk may further have a protective layer made of a carbon-based material such as diamond-like carbon and laminated on the magnetic layer, and a lubricating layer made of lubricating oil and applied on the protective layer.

[0076] B-2. Manufacturing method of magnetic disk When manufacturing a magnetic disk from an aluminum alloy substrate, for example, the following method can be adopted. First, the aluminum alloy substrate is degreased and washed to remove oils such as processing oils adhering to the surface of the aluminum alloy substrate. After the degreased and washed, the aluminum alloy substrate may be etched using an acid, if necessary. When etching is performed, it is preferable to perform a desmutting treatment after the etching to remove smut generated by the etching from the aluminum alloy substrate. The treatment conditions in these treatments can be appropriately set according to the type of treatment liquid.

[0077] After these plating pretreatments, a zincate treatment is performed to form a Zn film on the surface of the aluminum alloy substrate. In the zincate treatment, a zinc immersion plating is performed to replace Al with Zn, thereby forming a Zn film. As the zincate treatment, it is preferable to adopt a so-called double zincate method, in which the Zn film formed on the surface of the aluminum alloy substrate is once peeled off after the first zinc immersion plating, and a Zn film is formed by performing zinc immersion plating again. According to the double zincate method, a denser Zn film can be formed on the surface of the aluminum alloy substrate compared to the Zn film formed only by the first zinc immersion plating. As a result, defects in the Ni-P plating film can be reduced in the subsequent electroless Ni-P plating process.

[0078] After forming a Zn film on the surface of an aluminum alloy substrate by zincate treatment, the Zn film can be replaced by a Ni-P plating film by performing electroless Ni-P plating. As described above, if the amount of coarse Si-KO particles and Ti-B particles on the surface of the aluminum alloy substrate can be reduced, a dense, thin, and less-varying Zn film is formed on the surface of the aluminum alloy substrate after zincate treatment. Then, by replacing such a Zn film with a Ni-P plating film in electroless Ni-P plating, a smooth Ni-P plating film with fewer plating pits can be formed.

[0079] When the thickness of the Ni-P plating film is increased, the number of plating pits tends to decrease, and a smooth Ni-P plating film can be formed. Therefore, the plating thickness is preferably 7 μm or more, more preferably 18 μm or more, and even more preferably 25 μm or more. In practice, the upper limit of the plating thickness is about 40 μm.

[0080] By polishing the Ni-P plating film after the electroless Ni-P plating treatment, the smoothness of the surface of the Ni-P plating film can be further improved.

[0081] After the electroless Ni-P plating process (including the polishing process), a magnetic material is attached to the Ni-P plating film by sputtering to form a magnetic layer. The magnetic layer may be composed of a single layer, or may be composed of multiple layers having different compositions. After the sputtering, a protective layer made of a carbon-based material is formed on the magnetic layer by CVD. Next, a lubricating oil is applied on the protective layer to form a lubricating layer. In this manner, a magnetic disk can be obtained. EXAMPLES

[0082] Examples of an aluminum alloy plate and its manufacturing method, as well as an aluminum alloy substrate made from the aluminum alloy plate and its manufacturing method will be described below. Note that the specific aspects of these aluminum alloy plates and their manufacturing methods, as well as the aluminum alloy substrate made from the aluminum alloy plate and its manufacturing method are not limited to the aspects of the examples shown below, and the configurations can be appropriately changed from the examples without departing from the spirit of the present invention.

[0083] (1) Preparation of aluminum alloy plate The aluminum alloy sheets used for evaluation in this example were produced by the following method. First, a molten metal having the chemical components shown in Table 1 was prepared in a melting furnace. For the alloys other than B1, aluminum ingots with a B content of 0.0015% or less (not 0.0000%) were used, and for the alloy B1, aluminum ingots with a B content of 0.0025% were used.

[0084] [Table 1]

[0085] Next, the molten metal in the melting furnace was transferred, and an ingot was produced by the casting method shown in Table 2 described later. Next, the surface of the ingot was chamfered to remove the segregation layer present on the ingot surface. After chamfering, the ingot was subjected to a homogenization treatment by heat treatment under the conditions shown in Table 2. Next, hot rolling was performed under the conditions shown in Table 2 to obtain a hot-rolled sheet. Furthermore, cold rolling was performed under the conditions shown in Table 2 to obtain a cold-rolled sheet. Note that, for the materials other than B2, a protective cover was installed at a position separated from the roll device for hot rolling and cold rolling by the length shown in Table 2, and for B2, an aluminum alloy sheet was produced without installing a protective cover.

[0086] (2) Preparation of aluminum alloy substrate The aluminum alloy plate was punched to obtain a disk blank having an annular shape with an outer diameter of 98 mm and an inner diameter of 24 mm. The disk blank was then subjected to pressure annealing by holding the disk blank at a temperature of 320° C. for 3 hours while applying pressure from both sides in the thickness direction. Furthermore, the outer peripheral end face and the inner peripheral end face of each disk blank after pressure annealing were cut to obtain a disk blank with an outer diameter of 97 mm and an inner diameter of 25 mm. Then, the plate surface of each disk blank was ground so that the grinding amount was 10 μm. In this manner, a test material of an aluminum alloy substrate was produced.

[0087] (3) Evaluation of the distribution of Si-KO particles and Ti-B particles The method for evaluating the number of Si-KO-based particles and Ti-B-based particles in each of the above test materials is described below. Note that alloy No. B3 had too low strength because the Mg content was 0.0%, and it was deformed during cutting and could not be used for magnetic disks. In addition, alloy No. B4 had too high Mg content and too high strength, and cracks occurred during rolling, and it could not be used for magnetic disks. Therefore, in Comparative Examples 3 and 4 using alloys No. B3 and 4, the distribution of Si-KO-based particles and Ti-B-based particles was not evaluated.

[0088] The Si-KO and Ti-B particles in each of the above test materials were observed using a SEM. However, the observation range by SEM is several hundred μm. 2 Therefore, when the number of Si-KO-based particles and Ti-B-based particles with a maximum diameter of 1 μm or more present on the aluminum alloy substrate surface is extremely small, it is not practical to measure the number of Si-KO-based particles and Ti-B-based particles by observing the surface of each test material using a SEM. Therefore, in this example, the number of Si-KO-based particles and Ti-B-based particles with a maximum diameter of 1 μm or more was measured for each test material by the following method.

[0089] When the coarse Si-KO and Ti-B particles are not present on the surface of the aluminum alloy plate, scratches caused by the coarse Si-KO and Ti-B particles are not formed on the surface of the aluminum alloy substrate during cutting or grinding, so that an aluminum alloy substrate having a smooth surface can be obtained. As a result, plating pits are unlikely to be formed in the Ni-P plating film formed on the aluminum alloy substrate.

[0090] On the other hand, when coarse Si-KO and Ti-B particles are present on the surface of an aluminum alloy plate, scratches caused by the coarse Si-KO and Ti-B particles are formed on the surface of the aluminum alloy substrate during cutting or grinding. As a result, plating pits are likely to form in the Ni-P plating film on the aluminum alloy substrate directly above the scratches on the surface of the aluminum alloy substrate.

[0091] First, the surface of each aluminum alloy substrate test material was visually observed to confirm the presence or absence of scratches formed during cutting or grinding. Next, for test materials with scratches on the surface, the scratches and their surroundings were observed by SEM, and surface analysis was performed using EDS. Then, based on the SEM images obtained by the surface analysis, it was confirmed that Si-KO-based particles and Ti-B-based particles were present on the surface of each test material, as well as the longest diameter and number of the Si-KO-based particles and Ti-B-based particles.

[0092] The results are shown in Table 2. Table 2 shows the number of Si-KO-based particles and Ti-B-based particles with a maximum diameter of 1 μm or more present on the surface of each test material, that is, the number of Si-KO-based particles and Ti-B-based particles with a maximum diameter of 1 m or more present on the surface of the aluminum alloy substrate, measured over a 6000 mm 2 The value converted into the number of hits is shown.

[0093] [Table 2]

[0094] As shown in Table 2, in Examples 1 to 10 of the present invention, the alloy composition is specific as defined in the claims, and the number of Si-KO-based particles and Ti-B-based particles with a maximum diameter of 1 μm or more exposed on the surface of the test material is 1 / 6000 mm 2 Therefore, in these examples of the present invention, the formation of plating pits in the electroless Ni-P plating process is suppressed, and the smoothness of the Ni-P plating film can be improved.

[0095] On the other hand, in Comparative Example 1, alloy No. B1 with a B content of 0.0025% was used, and therefore many coarse Ti-B particles were present. The coarse Ti-B particles fell off during the process of producing the aluminum alloy substrate, causing dents and scratches on the surface. Therefore, in Comparative Example 1, when the aluminum alloy substrate produced from alloy No. B1 was subjected to electroless Ni-P plating treatment, the number of plating pits increased, and the smoothness of the Ni-P plating film decreased.

[0096] In Comparative Example 2, the aluminum alloy plate B2 was produced without a protective cover, so that dust from the surrounding environment was attached to and embedded in the surface of the aluminum alloy plate, resulting in the presence of many coarse Si-KO-based particles. The coarse Si-KO-based particles fell off during the process of producing the aluminum alloy substrate, causing dents and scratches on the surface. Therefore, in Comparative Example 2, when the aluminum alloy substrate produced from Alloy No. B2 was subjected to electroless Ni-P plating, the number of plating pits increased, resulting in a decrease in the smoothness of the Ni-P plating film.

[0097] As described above, in Comparative Examples 3 and 4 in which Alloy Nos. B3 and 4 were used, the distribution of Si-KO based particles and Ti-B based particles was not evaluated.

[0098] The present invention allows various embodiments and modifications without departing from the broad spirit and scope of the present invention. The above-described embodiments are for the purpose of explaining the present invention and do not limit the scope of the present invention. That is, the scope of the present invention is indicated by the claims, not the embodiments. Various modifications made within the scope of the claims and the scope of the invention equivalent thereto are considered to be within the scope of the present invention.

[0099] This application is based on Japanese Patent Application No. 2020-068369, filed on April 6, 2020. The entire specification, claims, and drawings of Japanese Patent Application No. 2020-068369 are incorporated herein by reference. [Industrial Applicability]

[0100] According to the present invention, it is possible to provide an aluminum alloy substrate for magnetic disks on which a Ni-P plating film having few plating pits and high smoothness can be formed by suppressing the generation of coarse Si-KO-based particles and Ti-B-based particles on the surface and reducing damage to the substrate surface due to the falling off of these particles.

Claims

1. The aluminum alloy contains 1.0 to 6.5 mass% Mg, the balance being Al and unavoidable impurities, and the distribution of Si-K-O type particles having a maximum diameter of 1 μm or more attached to the surface from the surrounding environment is 1 particle or less per 6000 mm 2 The distribution of Ti-B particles having a maximum diameter of 1 μm or more on the surface is 1 particle / 6000 mm 2 1. An aluminum alloy substrate for a magnetic disk, comprising:

2. The aluminum alloy substrate for magnetic disks according to claim 1, further comprising one or more selected from the group consisting of Cu: 0.300 mass% or less, Zn: 0.60 mass% or less, Fe: 0.600 mass% or less, Si: 0.600 mass% or less, Be: 0.0020 mass% or less, Cr: 0.20 mass% or less, Mn: 1.70 mass% or less, Zr: 0.20 mass% or less, Sr: 0.10 mass% or less, Na: 0.10 mass% or less, and P: 0.10 mass% or less.

3. 3. A magnetic disk comprising the aluminum alloy substrate for magnetic disks according to claim 1 or 2, on the surface of which an electroless Ni-P plating layer and a magnetic layer thereon are provided.

Citation Information

Patent Citations

  • Production of al base alloy plate for magnetic disc

    JP1981105846A

  • Aluminum substrate for magnetic disk

    JP1986076643A

  • Aluminum alloy for magnetic disk substrate

    JP1987007829A

  • Aluminum treatment method

    JP2002173718A

  • Substrate for magnetic disk, method for manufacturing the same, and magnetic disk using substrate for magnetic disk

    JP2019160384A